Solar Cells: Perovskite and Organic Solar Cells Fabricated by Inkjet Printing: Progress and Prospects (Adv. Funct. Mater. 41/2017). (2nd November 2017) - Peng, Xiaojin; Yuan, Jian; Shen, Shirley; Gao, Mei; Chesman, Anthony S. R.; Yin, Hong; Cheng, Jinshu; Zhang, Qi; Angmo, Dechan
Abstract : The pervasive use of non‐scalable fabrication methods in research greatly hinders the translation to industrial manufacturing of perovskite and organic solar cells. Inkjet printing is a scalable technique suitable for lab to industrial scale production. In article number1703704, Dechan Angmo and co‐workers comprehensively review inkjet printing application in the fabrication of different functional layers in organic and perovskite solar cells.